Informative and Goodwill Advertising - Boyer, Kenneth D. (The Review of Economics and Statistics, 1974)
T HIS paper attempts to show that there is merit in the long-standing but much abused distinction between 'informative' and other types of advertising, and that this difference is revealed in a differential effect on economic performance. After a brief literature survey, section II develops a theoretical distinction between informative and goodwill advertising. Section III outlines a test of the hypothesis that the different kinds of advertising will have opposite effects on market performance. Section IV presents the results of this test. Section V summarizes and relates the results to other recent work on the economics of advertising.